Profil Progesteron Air Susu dan Tingkat Kebuntingan Sapi Perah Pascasinkronisasi Estrus Menggunakan Prostaglandin F2Alfa atau Progesteron-CIDR (MILK PROGESTERONE PROFILE AND PREGNANCY RATE ON DAIRY CATTLE AFTER ESTROUS SYNCHRONIZATION WITH PROSTAGLANDIN F - Suprihatin, Novi; Tumbelaka, Ligaya ITA; Setiadi, Mohamad Agus (Jurnal Veteriner; Vol 17 No 3 (2016), 2016)
Research on estrus synchronization, progesterone profiles of post-synchronization and early pregnancyhas been conducted using 16 Holstein Frisian dairy cows. Treated cows were divided into 2 groups. Cowsin group I were synchronized with double injection of prostaglandin F2á (PGF2á, Lutalyse®) 25 mg / head at11 days apart, then were inseminated twice at 72 hours and 96 hours after the second injection of PGF2á(FTAI = fixed timed insemination). Group II were synchronized with progesterone implant-CIDR® for 11days. At the time of progesterone implant withdrawal the animals were injected with PGF2á at 25 mg /head then inseminated twice at 48 hours and 72 hours. Milk samples were collected on the day before, atthe treatment day and at day 1st, 3rd, 5th, 7th following the first insemination in order to determine theprofile of progesterone after synchronization, while for early pregnancy examinations, sampling of milkwere collected at day 21th, 24th and 27th after the first insemination. The milk samples were analyzed byRadioimmunoassay (RIA) method. Rectal palpation to confirm pregnancy was undertaken at day 60thafter the first insemination. The results showed a marked decrease in milk progesterone (nmol / l) at thefirst insemination (H0) in both group PGF2á and CIDR® (0.84; 0.49 vs. 0.92; 0.32), which indicated theoccurrence of estrus. Gradually increased of milk progesterone level (0.52; 0.68; 1.17; 1.69, respectively)started from day 1st, 3rd, 5th, 7th was seen in animals PGF2á group, whereas in the CIDR® group the milkprogesterone level was found fluctuate (0.21; 0.39; 0.33; 1.61). However, at day 7th the concentration ofprogesterone in both groups was significantly increased which indicated functional activity of the corpusluteum. Meanwhile the progesterone concentrations (nmol/l) of pregnant cows at day 21st, 24th and 27th ingroup PGF2á were 3.63; 3.51; 1.58 and in CIDR® group were 2.50; 2,79; 4.35, respectively. In non-pregnantcows, the progesterone concentrations (nmol/l) were lower (0.63; 0.42; 1.41 vs. 0.20; 0.27; 1.33), than thoseof pregnant cows. The results of rectal palpation after 60 days of the first Artificial Insemination (AI)confirmed that 5 cows with higher milk progesterone concentrations at day H21, H24, H27 from the firstinsemination were pregnant, with the possibilities at 62.5% in each group. It is concluded that estroussynchronization using either PGF2á or CIDR® in lactating dairy cows will give the same response and thiscould be detected using the milk progesterone profiles. Measurement of milk progesterone concentrationsby RIA began at day 21 of the first AI was effective for early pregnancy diagnosis.
Keywords: estrous synchronization, milk progesterone, pregnancy rate